Treatment options for steroid-dependent nephrotic syndrome. Issue 2 (April 2009) - Smith, Graham C
The term steroid-dependent nephrotic syndrome refers to a specific pattern of disease whereby relapses of nephrosis occur while on, or soon after stopping, steroids. While children remain responsive to steroids, they are expected to retain renal function and eventually grow out of the condition. Until that happens, the aim of treatment is to prevent relapses while minimizing the toxic effects of the medications used. Steroids remain the mainstay therapy, but children with steroid-dependent nephrotic syndrome can become exposed to large doses and the aim is then to use so-called ''steroidsparing'' strategies. This review discusses some of the more recent information available to help guide clinicians through this somewhat murky area of pediatric nephrology.